La medicina della mente: una presentazione a Milano - Vari, Autori (Il sogno della farfalla, 2012)
We are publishing the talks, and the debate that followed, of the book launch of La medicina della mente. Storia e metodo della psicoterapia di gruppo (Medicine for the mind. History and method of group psychotherapy) by Daniela Colamedici, Andrea Masini and Gioia Roccioletti, held on 13th January, 2012. The authors of the book, a collective work involving 40 psychiatrists and psychotherapists who all follow the research carried out by Massimo Fagioli and the Collective Analysis group, were present as were the journalists, Giovanna Pezzuoli and Gian Marco Walch. The presentation of the book offered, among other things, another occasion in which to stress the need for psychotherapy to acquire a medical approach, and the opportunity to reconstruct the characteristics and study the evolution of the setting of the Collective Analysis over time.